Applying Flash as an Interactive Media in Mastering Simple Present Tense at Junior High School: - - Djoko Sri Bimo; Binti Muflikah; Maria Yustina Rensi Dartani (ELT-Lectura, 2022)
Learning grammar is complicated, since it must understand the structure or formula in it, then there are many rules and patterns interrelated. The Simple Present Tense (SPT) is part of the grammar taught in junior high school. Learning the SPT for most students is very confusing, because the subject is considered quite difficult. And to minimize those difficulties faced by students in learning SPT, so the teachers try to make students understand the material by trying to make breakthroughs through the use of innovative learning media. Start from there, many creations related to the use of technology were created. Learning by involving technological sophistication more or less has a positive influence on students, since in addition to make it easier for them to learn, the teacher will also focus more on the material conveyed. Multimedia is a new concept and technology in the field of information technology, in where text, images, sound, animation and video are put together on a computer to be stored, processed and presented both linearly and interactively. This study aims to describe the implementation of interactive multimedia and to describe the success rate of grade VIII students of SMP Muhammadiyah 1 Surakarta in learning SPT. This study used a quantitative research approach, and it was a quasi-experiment. The experimental design was randomized pre-test and post-test comparison group design. The sample was class VIII PK-1 as the experimental group 1, while class VIII PK-2 as the experimental group 2. The sample was taken by using cluster random sampling technique. With this interactive multimedia learning method, it is expected that the participants’ ability in mastering English grammar can be improved.